Pemeliharaan Sarana dan Prasarana Ruang Kelas di SMP Negeri 5 Satu Atap Pangkalan Lampam - Afmitiani, Sinka; Setyaningsih, Kris; Maryance, Maryance (Indo-MathEdu Intellectuals Journal, 2024)
Maintenance of educational facilities and infrastructure involves managing and organizing these resources to ensure they are always in good condition and ready for use to achieve educational goals. This research aims to investigate the maintenance of classroom facilities and infrastructure at SMP Negeri 5 Satu Atap Pangkalan Lampam. The type of research used is qualitative, with data collection techniques including observation, interviews, and documentation. The techniques used in data analysis are data reduction, data presentation, and conclusion drawing. The validity of the data in this research is ensured through time triangulation, technique triangulation, and source triangulation. The results indicate that the maintenance of classroom facilities and infrastructure at SMP Negeri 5 Satu Atap Pangkalan Lampam is quite good. This is evident from the awareness, understanding, organization, implementation, and documentation aspects. Supporting factors include adequate funding and good cooperation between teachers and students in classroom maintenance activities. The inhibiting factors are mainly due to a lack of awareness and understanding among students regarding the maintenance of classroom facilities and infrastructure.